Body and Conflict: The Interplay of Genre, Gender, and Lebanese Realities in Nadine Labaki’s Cinema - Woroch, Adrianna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The article presents the work of Lebanese filmmaker Nadine Labaki in the context of a woman’s vision of a world filled with dichotomies. In all three films discussed – Caramel (2007), Where Do We Go Now? (2011) and Capernaum (2018) – she shares a specific tension, balancing between tenderness and cruelty, between the everyday beauty of life and its unbearable burden. In genre formulas, often seemingly light-hearted, rich in slapstick gags and musical elements, she tells stories from the perspective of mothers, daughters or lovers, presenting their vision of how to maintain hope amid the absolute terror of the outside world. Labaki brings out of this disharmony stories full of empathy, humour and pain, which draw the viewer into an intricate and morally ambiguous world of emotion and reflection. In the article, I will look at the extent to which the director’s feminine, subtle sensibility allows her to create cinema that is both commercially acceptable and deeply artistic, and at what points she uses elements of genre cinema (humour, sexuality, eroticism) to speak of the chaos of the world and its injustice.